Roosevelt Island: Completing an Urban Community - Kilgore, Karin M. (SURFACE at Syracuse University, 1999)
"The thesis became an architectural exploration of what makes neighborhoods and community at two scales: at the scale of the city (macrocosm), represented by the urban plan; and at the scale of the individual (microcosm), represented by the concept of house and housing. At these two contrasting scales, the main focus of the study was: To explore how an urban design can shape community; To explore the role housing plays in the making of urban fabric/neighborhood."